2022
DOI: 10.3390/ma15217666
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Fractal Dimension and Properties of Engineered Cementitious Composites with Different Aggregates

Abstract: In this study, the effects of different fine aggregates on the properties of polyethylene fiber engineered cementitious composite (PE-ECC) were systematically investigated. The PE-ECCs were prepared with four fine aggregates, respectively. Furthermore, their flowability, compressive strength, and uniaxial tensile properties were studied experimentally and comparatively analyzed by microscopic techniques including X-ray diffraction (XRD), scanning electron microscope (SEM), energy-dispersive spectroscopy (EDS),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Table 3 shows the flowability and setting time values with change in fibre content. In general, the flow value of all the mixes remained in the range similar to that of engineered cementitious composites [35]. Moreover, though the setting time did not show any clear trend with change in fibre dosage, a comparison could be made with the values without fibres as reported by Guo et al [21].…”
Section: Fresh Propertiessupporting
confidence: 56%
“…Table 3 shows the flowability and setting time values with change in fibre content. In general, the flow value of all the mixes remained in the range similar to that of engineered cementitious composites [35]. Moreover, though the setting time did not show any clear trend with change in fibre dosage, a comparison could be made with the values without fibres as reported by Guo et al [21].…”
Section: Fresh Propertiessupporting
confidence: 56%
“…The DS particles were fine and filled the gaps between the aggregates, as shown in Figure 10 b, which could explain the phenomenon of the apparent density and compressive strength of the FDCC increasing when the DS replacing ratio reached a certain level. However, slight cracks appeared at the edges of the DS particles ( Figure 10 b), which formed a weak position and became damaged under mechanical action because the DS surface was relatively smooth, meaning that damage occurred more easily at the interfaces [ 37 ].…”
Section: 5 Sem Analysismentioning
confidence: 99%
“…Xia [14] investigated the effects of four different fine aggregates on the mechanical properties of HE-ECCs. The results showed that the different types of fine aggregates have little effect on the fluidity of PE-ECCs but have a relatively great effect on the compressive strength, uniaxial tensile strength, and ultimate tensile strain.…”
Section: Introductionmentioning
confidence: 99%